Implementation of Green Government by the Regional Government of East Kalimantan Province as a Form of Ecological Principles (Case Study of the Impact of the Implementation of Coal Mining Policy in Samarinda City) - Melati Dama; Sry Reski Mulka; Nur Hasanah; Jauchar Barlian (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study raises the theme of implementing green government in Samarinda City in upholding the principles of ecology in the region. How is the relation between the capitalistic paradigm in the implementation of local government politics with the implementation of green government in realizing ecological principles? In analyzing the implementation of green government, it can be seen how the local government responds in responding to the impact of coal mining activities in the city of Samarinda in accordance with the principles of ecology. The method used is a documentation study with a descriptive approach the data sources come from journals, books and research reports. Based on the findings that the Regional Government is unable to implement green government in supporting the realization of the environmentally friendly Samarinda City, this can be seen from the rampant environmental damage caused by coal mining activities. The implementation of green government by the Regional Government in realizing the principles of ecology in Samarinda City is not working because the old paradigm used by the government is still strong in implementing regional development that relies on profit accumulation.